Antibiotics versus no therapy in kidney transplant recipients with asymptomatic bacteriuria (BiRT): a pragmatic, multicentre, randomized, controlled trial. (March 2021) - Coussement, Julien; Kamar, Nassim; Matignon, Marie; Weekers, Laurent; Scemla, Anne; Giral, Magali; Racapé, Judith; Alamartine, Éric; Mesnard, Laurent; Kianda, Mireille; Ghisdal, Lidia; Catalano, Concetta; et al.
Abstract: Objectives: Many transplant physicians screen for and treat asymptomatic bacteriuria (ASB) during post-kidney-transplant surveillance. We investigated whether antibiotics are effective in reducing the occurrence of symptomatic urinary tract infection (UTI) in kidney transplant recipients with ASB. Methods: We performed this multicentre, randomized, open-label trial in kidney transplant recipients who had ASB and were ≥2 months post-transplantation. We randomly assigned participants to receive antibiotics or no therapy. The primary outcome was the incidence of symptomatic UTI over the subsequent 12 months. Results: One hundred and ninety-nine kidney transplant recipients with ASB were randomly assigned to antibiotics (100 participants) or no therapy (99 participants). There was no significant difference in the occurrence of symptomatic UTI between the antibiotic and no-therapy groups (27%, 27/100 versus 31%, 31/99; univariate Cox model: hazard ratio 0.83, 95%CI: 0.50–1.40; log-rank test: p 0.49). Over the 1-year study period, antibiotic use was five times higher in the antibiotic group than in the no-therapy group (30 antibiotic days/participant, interquartile range 20–41, versus 6, interquartile range 0–15, p < 0.001). Overall, 155/199 participants (78%) had at least one further episode of bacteriuria during the follow-up. Compared with the participant's baseline episode of ASB, the second episode of bacteriuria was more frequently caused by bacteria resistant to clinically relevant antibiotics (ciprofloxacin, cotrimoxazole, third-generation cephalosporin) in the antibiotic group than in the no-therapy group (18%, 13/72 versus 4%, 3/83, p 0.003). Conclusions: Applying a screen-and-treat strategy for ASB does not reduce the occurrence of symptomatic UTI in kidney transplant recipients who are more than 2 months post-transplantation. Furthermore, this strategy increases antibiotic use and promotes the emergence of resistant organisms.